Enhancing phytochemical content and bioactive aspects in somatic embryogenesis developed from callus of Phoenix dactylifera L. - Ammar M.A. ALI; Ahmed A. QAHTAN; Jameel M. AL-KHAYRI; Methaq N. ALGABR; Othman M. AL-DOSSARY; Bader ALSUBAIE (Notulae Botanicae Horti Agrobotanici Cluj-Napoca)
This research aims to investigate the chemical profile of methanolic (MeOH) extracts of callus and somatic embryogenesis (SE) induced from date palm ‘Barhi’ cv. (Phoenix dactylifera L.) by total polyphenols estimation and gas chromatography-mass spectrometry (GC-MS) analysis. In addition, some biological aspects as antiradical and anti-enzymes inhibitory effects were evaluated by in vitro examinations. Results demonstrated that, total phenol content (TPC) and total tannin content (TTC) were significantly increased by 14.95% and by 16.83%, respectively, in callus than that estimated in SE. Whereas total flavonoid content (TFC) in SE recorded a very high increase rate of 564.4% above that found in callus. GC-MS chromatogram of SE extract had more phytochemicals about 35 molecules were identified, including five specific bioactive compounds with considered ratios ranging between 2.265% and 12.76%. Overall, the determined biological aspects were significantly improved (p < 0.05) in SE, particularly anti-Diphenyl-2-picryl-hydrazyl (DPPH), Ferric Reducing Antioxidant Power (FRAP), and Total Antioxidant Capacity (TAC) by 48%, 92.31%, and 54.35% sequentially as antiradical/antioxidant potentials in terms of IC50 values. Furthermore, anti-α-amylase and anti-α-glucosidase effects were enhanced by 2,750% and 224.16%, respectively, in SE compared to callus results. In summary, MeOH extract of SE was richer in phytochemicals with greater bioactive properties than callus; this evaluated superiority could be attributed to the developmental and morphological differentiation occurring for SE tissues, which may be a prerequisite for greater content production and accumulation of many types of bioactive secondary metabolites. Further prospective pharmacological studies are required to recommend SE of ‘Barhi’ cv. as a natural nutritional and therapeutic source.